Hybridity as a Strategy For Self-Determination in Contemporary American Indian Art - Fowler, Cynthia (Social justice, 2007)
Part of a special issue on the relationship between art, identity, and social justice. Self-determination remains an important concern for many Native Americans and is reflected in contemporary Native American art. Indeed, Native American artists working from the 1990s to the present have consistently used a variety of strategies to create politically charged art intended to define their culture on its own terms. From celebrations of indigenous cultures and values to exploring the meaning of sovereignty for native peoples within the U.S., these artists seek to redefine their identities, traditions, values, and cultural identities while also exposing institutional oppression that denies indigenous peoples the ultimate objective of self-determination. A particular strategy that emerged in this regard in the 1990s is that of engaging the postcolonial idea of hybridity, a strategy that a key group of contemporary Native American artists continues to use.